2017
DOI: 10.1371/journal.pone.0169874
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Host-Related Variation in Prevalence and Population Density of Wheat Curl Mite (Aceria tosichella) Cryptic Genotypes in Agricultural Landscapes

Abstract: The wheat curl mite (WCM), Aceria tosichella Keifer, is a major pest of cereals worldwide that also comprises a complex of at least 16 genetic lineages with divergent physiological traits, including host associations and specificity. The goal of this study was to test the extent to which host-plant species and landscape spatial variation influence WCM presence and population density across the entire area of Poland (>311,000 km2). Three important findings arose from the results of the study. (1) The majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The WCM was identified as the agent transmitting WSMV by Slykhuis (), and the recent use of DNA sequence data and experimental host bioassays has shown that the WCM is, in fact, a species complex consisting of several divergent genetic lineages (probably cryptic species) (Miller et al ., ; Skoracka et al ., ). Some lineages are highly host specific to single wild‐growing grass species, whereas others are less host specialized and feed on several plant species, including cereals (Skoracka et al ., ). The genetic and host range variability within the WCM complex corresponds to the virus vectoring ability amongst WCM lineages (Hein et al ., ; Schiffer et al ., ).…”
Section: Virus Transmission By Wcmmentioning
confidence: 99%
See 1 more Smart Citation
“…The WCM was identified as the agent transmitting WSMV by Slykhuis (), and the recent use of DNA sequence data and experimental host bioassays has shown that the WCM is, in fact, a species complex consisting of several divergent genetic lineages (probably cryptic species) (Miller et al ., ; Skoracka et al ., ). Some lineages are highly host specific to single wild‐growing grass species, whereas others are less host specialized and feed on several plant species, including cereals (Skoracka et al ., ). The genetic and host range variability within the WCM complex corresponds to the virus vectoring ability amongst WCM lineages (Hein et al ., ; Schiffer et al ., ).…”
Section: Virus Transmission By Wcmmentioning
confidence: 99%
“…In Poland, these two WCM biotypes also differ in colonization strategy, and biotype 1 (MT‐8) has a uniform distribution, whereas biotype 2 (MT‐1) occurs unexpectedly in only a few localities within the country, but attains very high densities there (about 30% higher than MT‐8) (Skoracka et al ., ). All results obtained to date now suggest that biotype 2 (MT‐1) is able to multiply more rapidly and transmit WSMV more efficiently than biotype 1 (MT‐8).…”
Section: Virus Transmission By Wcmmentioning
confidence: 99%
“…MT-8 and MT-1 have been found coexisting in mixed populations in wheat-producing areas in North America, Australia, and Europe, where plants from a single wheat field contained both MT-1 and MT-8 ( Siriwetwiwat, 2006 ; Schiffer et al, 2009 ; Hein et al, 2012 ; Skoracka et al, 2017 ), further complicating management of viruses vectored by WCM. This sympatry combined with differential virus-transmission accentuates the need for efficient identification methods.…”
Section: Wcm Diversity and Its Implicationsmentioning
confidence: 99%
“…Two biotypes of A. tosichella that co-occur in North America exhibit different virulence responses to Cmc wheat mite-resistant genes and genetic variability [9,11]. Although A. tosichella biotype composition and distribution in U.S. barley production areas has yet to be determined, biotypes 1 (MT-8) and 2 (MT-1) collected from barley in Poland's agrarian landscape occurred at mean densities of 9.7 and 19.3 mites per shoot, respectively [12]. Furthermore, the Polish biotype 2 collected from wheat and reared on susceptible barley plants exhibited a >40-fold increase in population growth rate in 14 days [10], providing evidence that this biotype has the ability to use barley as a host.…”
Section: Introductionmentioning
confidence: 99%